The Allergy Management of Bronchial Asthma in Children in Surabaya - Harsono, Ariyanto; Partana, Js.; Partana, L. (Indonesian Pediatric Society, 1990)
The allergy management of bronchial asthma consists of avoidance of exposure to allergens either inhalant, or ingestant, hyposensitization in cases where complete avoidance is impossible and drug therapy is needed. The diet initiated in allergic children is principally a diagnostic tool. There are two important diet regimens. First, ''The Elimination Diet', indicated in patients to exclude major allergenic foods such as fruit, milk, egg, fish, and peanut Secondly, ''The Minimal Diet'' (Modified Rowe's Diet), consisting of several foods ''allowed'' such as water, rice, coconut, beef, soy-cake, soy sauce, spinach, carrot, garlic and onion, salt and sugar, while other foods are prohibited. To obtain clear improvement of symptoms, the diet must be continued for 3 weeks. If improvement occurs, a challenge can be performed. All previously excluded foods can be reinstituted one at a time in a sufficient amount, every day for one week. If no symptoms appear, the food can be considered as non allergenic to the patient. If symptoms reappear, the food should be suspected as causing the allergy. For diagnosis, three challenges are required. Pharmacologic therapy is initiated with ephedrine and chlortrimeton as needed. Aminophylline and beta 2 agonist may be given as a substitute if the former drugs fail to relieve the symptoms. Intravenous aminophylline and corticosteroid are used especially in ''status asthmaticus''.